Aplikasi Edible Coating Albedo Semangka dengan Penambahan Ekstrak Etanol Daun Bandotan pada Tomat Napu: Application of Edible Coating of Watermelon Albedo with the Addition of Ethanol Extract of Bandotan Leaves on Napu Tomato - Lutfi, Mohammad; Wulandari, Asri; Fito; Rahmadina, Hizra Nur; Chaedar, Nur; Nurhaeni; Amar, Aini Auliana (KOVALEN: Jurnal Riset Kimia, 2024)
One of the causes of food waste is due to the lack of post-harvest handling of fruits or vegetables, therefore, an innovation is needed to overcome this problem, one of which is with edible coating. This study aimed to determine the characteristics of edible coatings from watermelon albedo pectin with the addition of Bandotan leaf extract as an antibacterial against Napu tomatoes. This study used a completely randomized design (CRD) consisting of 4 treatments, namely tomatoes (edible coating), tomatoes (edible coating + 12.5% bandotan leaf ethanol extract), tomatoes (edible coating + 25% bandotan leaf ethanol extract), and tomatoes (edible coating + 50% bandotan leaf ethanol extract). The watermelon albedo pectin characterization test results were the equivalent weight of 558.3 mg, methoxyl content of 6.1%, galacturonic acid content of 32.1%, moisture content of 11.469%, and ash content of 9.378%. From the results of tomato characterization tests for weight loss, moisture content, and microbial tests, the best treatment was produced by tomatoes (edible coating + 50% antibacterial), with consecutive results of 7.90%, 53.18%, 16.6 colonies (10-4 dilution), and 5.6 colonies (10-5 dilution).